2003
DOI: 10.1074/jbc.m211034200
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Disialyl Lewis a (Lea) Structure in Colon Cancer Cell Lines by a Sialyltransferase, ST6GalNAc VI, Responsible for the Synthesis of α-Series Gangliosides

Abstract: Biosynthesis of disialyl Lewis a (Le

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 23 publications
(24 reference statements)
4
64
0
1
Order By: Relevance
“…Some of the data were essentially the same as reported in [21] and [23], but they were confirmed in this study using the identical conditions. Both enzymes showed activity toward fetuin, MSGG and sialyl Lc4 as well as GM1b.…”
Section: Hst6galnac III and Vi Synthesize Dsggsupporting
confidence: 77%
See 2 more Smart Citations
“…Some of the data were essentially the same as reported in [21] and [23], but they were confirmed in this study using the identical conditions. Both enzymes showed activity toward fetuin, MSGG and sialyl Lc4 as well as GM1b.…”
Section: Hst6galnac III and Vi Synthesize Dsggsupporting
confidence: 77%
“…MSGG and DSGG were eluted from the DEAE-Sephadex by step-wise elution with sodium acetate (0.2, 0.25, 0.3, 0.45, 0.6 and 0.8 M) in a solvent system of chloroform/methanol/sodium acetate (30:60:8, by vol.). GM1b, sialyl Lc4, and sialyl nLc4 (see Table 2) were prepared as described previously [21].…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, however, more direct evidence of the contribution of incomplete synthesis the enhanced expression of sialyl Lewis a/x has been accumulated; i.e., further modified forms of sialyl Lewis x and sialyl Lewis a determinants were found to be significantly expressed in non-malignant colonic epithelium, namely, sialyl 6-sulfo Lewis x 27) and disialyl Lewis a [45][46][47] (Fig. 7).…”
Section: The Concept Of Incomplete Synthesis and Induction Of Sialyl mentioning
confidence: 99%
“…The human sialyltransferase ST6GalNac V, a member of the ST6GalNac family of sialyltransferases, is a type II Golgi membrane protein that transfers sialic acid from the donor CMP-Neu5Ac to the GalNac residue on the ganglioside, GM1b, forming GD1␣. Tsuchida et al (21) proposed indirect involvement of siat7e in synthesizing disialyl Le a , a carbohydrate structure conjugated to proteins and ceramides on the cell surface. In other studies, glycosphingolipids including gangliosides have been reported to mediate cell adhesion through the sugar residue interactions in the glycosynapse microdomains (22,23).…”
mentioning
confidence: 99%